2007
DOI: 10.1586/14779072.5.4.777
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone replacement therapy and modulation of vascular function in cardiovascular disease

Abstract: Epidemiological and experimental studies suggest vascular protective effects of estrogen. Cardiovascular disease (CVD) is less common in premenopausal women than in men and postmenopausal women. Cytosolic/nuclear estrogen receptors (ERs) have been shown to mediate genomic effects that stimulate endothelial cell growth but inhibit vascular smooth muscle proliferation. However, the Heart and Estrogen/Progestin Replacement Study (HERS), HERS-II and Women's Health Initiative clinical trials demonstrated that hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 80 publications
1
40
0
Order By: Relevance
“…Additionally, Bhasin et al (2010) recommend testosterone therapy only for men with consistent symptoms of androgen deficiency and unequivocally low serum testosterone levels. These researchers author found controversial results from androgenic therapies depending of the age of the patients (Spitzer et al, 2013), and this result is in agreement with the observations reported by Koledova and Khalil (2007). However, these researchers found that the administration of T with low-intensity physical training improves grip strength, spontaneous movements, and respiratory activity.…”
Section: Risks and Benefits Of Replacement Therapy With Sex Hormones:supporting
confidence: 79%
See 1 more Smart Citation
“…Additionally, Bhasin et al (2010) recommend testosterone therapy only for men with consistent symptoms of androgen deficiency and unequivocally low serum testosterone levels. These researchers author found controversial results from androgenic therapies depending of the age of the patients (Spitzer et al, 2013), and this result is in agreement with the observations reported by Koledova and Khalil (2007). However, these researchers found that the administration of T with low-intensity physical training improves grip strength, spontaneous movements, and respiratory activity.…”
Section: Risks and Benefits Of Replacement Therapy With Sex Hormones:supporting
confidence: 79%
“…Another therapeutic approach may involve the use of specific ER modulators (SERMs), which minimize the adverse effects of HRT, including breast cancer. Thus, the beneficial effects of HRT in postmenopausal vascular disease can be enhanced by customizing the HRT type, dose, route of administration, and timing depending on the subject's age (Koledova and Khalil, 2007). Therefore, the use of specific phytoestrogens or SERMS as an alternative therapy could be employed to correct alterations of estrogen deficiency or to decrease malignancy outcomes if these compounds are prescribed correctly.…”
Section: Risks and Benefits Of Replacement Therapy With Sex Hormones:mentioning
confidence: 99%
“…32 Furthermore, several studies have shown different effects of different progestins on endothelial function and thrombotic risk. [32][33][34][35] The WHI study has shown that in nonhysterectomized women receiving CEE-MPA in continuous combined scheme increased cardiovascular events in elderly PMW, whereas this was not the case in women receiving CEE alone. 10,11 Limitations of the present study are the lack of placebo control and of the adjunctive use of progestins.…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of evidence from observational and experimental studies, in both animals and humans, supports the concept of a protective effect of estrogens on the cardiovascular system (Koledova & Khalil 2007). Thus, it was wholly unexpected when the Women's Health Initiative, a large-scale trial of hormone replacement therapy (HRT) in postmenopausal women, was terminated early due to a surprising increase in the incidence of cardiovascular events (Hsia et al 2006).…”
Section: Introductionmentioning
confidence: 99%